Fair Innings: Equality and Children’s Healthcare - Long, Katherine; Zlotnik Shaul, Randi (BioéthiqueOnline, 2017)
This commentary assesses the ethical implications of a fair innings inspired approach to healthcare through the lens of the equality guarantee contained in the Canadian Charter of Rights and Freedoms.